FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP LAMANYA PERAWATAN PADA PASIEN PASCA OPERASI LAPARATOMI - Kusumayanti, Putu Devi (Coping: Community of Publishing in Nursing; Vol 3 No 1 (2015): JURNAL EDISI JANUARI-APRIL 2015, 2015)
Laparotomy is a major surgical that doing at abdomen area. Slashes on laparotomy's surgical makes large and deeply wound, because of that it needs treatment in the hospital for several days. During treatment, post laparotomy’s surgical patients needs more attention to prevent complication, minimalized days in hospitalized and cost of the treatment, for patients or management of the hospital. This study aimed to determine the influence factors for longer treatment of post operative laparotomy’s patients in hospitalization in the BRSU Tabanan. This is description observasional design with kohort prospection design, which data of independent variabel (influence factors) identified before, then followed as prospective till dependent variabel occur, that is the longer of hospitalization. Observation or measured variabel performed during four days, then the results analysis by the Spearman rank with level of significant ?=0,05. Samples consist of 19 patients were hospitalized in BRSU Tabanan, they were selected with purposive sampling technique. Data was collected using observation’s check list. Research results mean of there was relationship with age (?=0,05), nutrition intake (?=0,033), pain scale (?=0,016), early mobilization (?=0,033), with hospitalization’s longer on post laparotomy’s surgical patients in BRSU Tabanan. Based on that invention, there are some suggest to nursing to give more attention for ages, pain scale, nutrition intake, and early mobilization to post  laparotomy’s surgical patients, there for the hospitalization’s day on post laparotomy’s surgical patients can shorten.
Keywords: Ages; nutrition intake on post surgical, pain scale; early mobilization; hospitalitation’s days